Première observation d’un comportement de Leaf Swallowing chez des chimpanzés vivant en captivité à la Réserve Africaine de Sigean, France - Nathan Cazelles-Durand; Ulrich Maloueki; Lyna Rachid; Marielle Beltrame; Fanny Juillard; Désiré Musuyu-Muganza (Revue de Primatologie)
Leaf Swallowing (LS) is an atypically slow consumption of often rough leaves, which are rolled and swallowed, one by one, without chewing. This method seems to promote the expulsion of intestinal parasites and/or increase intestinal transit. We report observations of this type of behaviour in a population of chimpanzees (Pan troglodytes) living in captivity at the African reserve of Sigean (RAS), in France. Nine chimpanzees were provided with smooth, non-rough leaves of a plane tree (Platanus hispanica) and with rough, hispid leaves of a black mulberry (Morus nigra). All these individuals were presumed naive to LS because this behaviour had never been observed in this population before the study. This observation of LS behavior in naive chimpanzees supports the theory of a predisposition to the realization of LS with rough leaves, probably by individual learning. We also note the important role of social learning (facilitation and imitation) in the LS behaviour spread within the group. Indeed, some chimpanzees which initially rejected or chewed black mulberry leaves, then fold and swallow them (LS) after observing a congener demonstrator. Observation of LS in this healthy chimpanzee population (parasite-free, no noticeable intestinal discomfort) supports the hypothesis that LS originates from an opportunistic feeding behavior of primates in nature and not from an innate knowledge of the therapeutic property of this form of consumption. LS may simply be a spontaneous reaction to an unfamiliar leaf roughness. In this study, LS occurred with M. Nigra leaves, while this kind of behaviour was not observed with the leaves of the same species in a previous study. This allows us to refute the hypothesis of the existence of a roughness threshold, common to all chimpanzees, which would systematically trigger LS behavior.